2002
DOI: 10.1097/00045391-200207000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Oral Activated Charcoal in the Treatment of the Self-Poisoned Patient: A Prospective, Randomized, Controlled Trial

Abstract: Oral activated charcoal (OAC) is a universally accepted treatment of the overdose patient. Although the benefits of OAC have been suggested, there are no conclusive clinical data indicating that OAC affects outcome in overdose patients. This study was a prospective, randomized, controlled trial to determine the effects of OAC treatment in the self-poisoned adult patient. Adult patients presenting to the emergency department (ED) with a history of oral overdose were assigned to treatment with OAC (50 g) or supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 28 publications
3
29
0
1
Order By: Relevance
“…This incidence of vomiting was identical to the no activated charcoal arm of the previously mentioned randomized control trial by Merigian et al [19].…”
Section: Emesissupporting
confidence: 78%
See 1 more Smart Citation
“…This incidence of vomiting was identical to the no activated charcoal arm of the previously mentioned randomized control trial by Merigian et al [19].…”
Section: Emesissupporting
confidence: 78%
“…Many would not hesitate to administer activated charcoal to a comatose patient who presents within 1 h to the emergency department (ED) and has a protected airway; however, the debate seems to focus on the alert and awake patient, with stable vital signs. In a prospective, randomized, controlled study, Merigian et al [19] compared clinical outcome in 1479 self-poisoned patients receiving activated charcoal and supportive care or supportive care alone. They compared the incidence of vomiting, length of stay, and incidence of complications associated with the overdose or the treatment between the two groups.…”
Section: Benefitsmentioning
confidence: 99%
“…Recent adult studies comparing these 2 therapies, excluding clearly toxic ingestions, revealed no difference in outcome in those patients who were treated with supportive care and observation alone. 22,23 A retrospective study of children presenting with poisoning during 3 periods during which there was a decreasing use of gastric decontamination with SDAC also revealed no difference in their outcomes. 21 Given the existing practice variation, 4 -7 the evidence in adults supporting observation alone in all but the most toxic ingestions, and the possible increased risk of SDAC therapy in the pediatric patient, this study highlights the need for a prospective trial of SDAC versus observation alone in a pediatric population, excluding those with toxic acute ingestions.…”
Section: Discussionmentioning
confidence: 99%
“…6 Patients who had taken an acute drug overdose were treated with SDAC on even days of the month and supportive treatment alone on odd days. Patients who had ingested a potentially toxic dose of paracetamol (.140 mg/kg) were excluded (paracetamol accounts for 50% of self poisonings in the UK).…”
Section: Does Sdac Change Patient Outcome?mentioning
confidence: 99%